Izkustveno učenje bodočih vzgojiteljev predšolskih otrok - Jurka Lepičnik-Vodopivec (Journal of Elementary Education, 2008)
Learning from Work-Experience for Future Pre-School Teachers. This article focuses on the theory and practice of how future pre-school teachers learn from work-experience. Emphasis was put on the characteristics of several historical models of professional education. Special emphasis was given to the reflective model, which emphasizes the importance and role of practical experience. Pedagogic praxis is regarded as a part of the professional education of future educators, where learning takes place with the help of hands on experience and reflecting on one’s own practice.COBISS ID: 16221192